Installation of Waste Education Signage to Raise Environmental Awareness in the Nepo Village Tourism Area - Muhlis Muhlis; Nurcaya Nurcaya; Darmawan Sanusi; Ahmad Ghazali; Sitti Aminah; Besse Sulfiani; Indra Pratama Ali Aman; Hikmah Nurfadillah; Erviana Abdullah; Dwi Ahmadi Ahsari (Universitas Muhammadiyah Sidenreng Rappang, 2026)
The main problem in the Gelora Wisata area of ​​Nepo Village is the low level of visitor awareness regarding cleanliness, despite the availability of trash bins. This leads to a buildup of trash, which disrupts the aesthetics and health of the environment. This community service activity aims to raise visitor awareness by installing educational boards on proper waste management. The methods used included field observation, identifying critical points of waste accumulation, and installing informative visual educational materials about waste decomposition times. The results of this activity demonstrated a change in visitor behavior, with visitors beginning to heed the instructions on the boards and utilizing the available trash bins. In conclusion, strengthening visual education has proven effective in stimulating behavioral change in the tourism area